Steve Dobrogosz's 'When Lilacs Last in the Dooryard Bloom'd': A Conductor's Perspective - George-Twyman, William (My University, 2020)
Swedish composer Steve Dobrogosz (b. 1956) is primarily known for his jazz piano and songwriting career, having been an influential figure in the Stockholm musical scene since the 1980’s. Eventually he began to explore traditional notated composition and, following the international success of his Mass (1992) for choir, piano, and strings, Dobrogosz’s compositional style became more refined while retaining its exploratory nature. His compositions currently number in the thousands, including significant choral/orchestral works like the Requiem (2001), Christmas Cantata (2003), Stabat Mater (2012), and When Lilacs Last in the Dooryard Bloom’d (2000). Dobrogosz is a master of creating full, luxuriant sonic textures that require careful treatment of text. This document is an analysis of Steve Dobrogosz’s choral/orchestral setting of Walt Whitman’s pastoral elegy When Lilacs Last in the Dooryard Bloom’d. Contained within the paper are sections covering biographical information of the both the composer and the poet Walt Whitman, Dobrogosz's compositional approach and style, and a detailed musical analysis of each of the six movements that dissects form/thematic structure, tonality, texture, thematic construction, meter/rhythm, and harmony. The analysis pays particular attention to the synthesis of Walt Whitman’s unmetered free verse and Dobrogosz’s lyrical melodic constructions, illustrating Dobrogosz’s masterful handling of complicated poetic material.
Keywords: Choral Conducting; Choral Music; Steve Dobrogosz; Swedish Music